Disorder effects in the S1⁄41 antiferromagnetic spin ladder CaV2O4 - Guitarra, S.R.; Caneiro, Alberto; Niebieskikwiat, Dario Gabriel (Elsevier Science, 2015)
Fil: Guitarra, S.R.. Universidad San Francisco de Quito; Ecuador